(3GdTeSjIs - (3GdcGJHj GdbRhjfj, fLe GdOjf, OHjQGf, Ydj Hf YeQ Hf Ydj, (B675 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI Cbhd GdQSGdI eQJHI Ydi ebOeI hKdGK ebGdGJ hNGJeI , CeG GdebOeI eGgjI GdefWb hHjGf GdMGLI Edjg hehVhYg CeG GdebGdGJ aChdgG aj GdeaQOGJ hGdKGJjI GdbVGjG (B...s
(3BNQgG (B:s
... (3agj GdGYQGV GdPGJjI dehVhY GdYdhe adGHO Cf jchf NGQLI Yf ehVhYGJgG dGeJfGY Cf jchf LRA GdTjA eWdhHG HGdQgGf dGf GdCLRGA (B... (3GdKHhJ , hdjcf gPG BNQ eG CQOfG EjQGOgs
(3aj Chdg ahGFO HebOGQ hQbJjfs
(3JHUQI GdeDda (B:s
(3fSHgG UGMH GdcTa d YeQ Hf Ydj , dcf GdRcdj hcMGdg fSHGgG dYdj Hf YeQ Hf Ydjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\315s
(3cTa GdXfhf (B2\1063s
Keywords: (3GdadSaI hGdefWbs